In vivo ketogenic diet treatment attenuates pathologic sharp waves and high frequency oscillations in in vitro hippocampal slices from epileptic K(v)1.1α knockout mice - Simeone, Timothy A. (2014)
The ketogenic diet (KD) is an effective therapy for pediatric refractory epilepsies, however, whether the KD changes the pathologic network oscillations generated by an epileptic brain remains unknown. We have reported that hippocampal CA3 regions of epileptic Kv1.1α knockout (KO) mice generate pathologic sharp waves (SPWs) and high frequency oscillations (HFOs) that have higher incidence, longer duration and fast ripples compared to wild-type. Synaptic activity of hyperexcitable KO mossy fibers significantly decreased CA3 principal cell spike-timing reliability contributing to this network pathology. Also, we have demonstrated that the KD reduces seizures by 75% in KO mice. Here, we determined whether 10-14 day in vivo KD treatment exerts disease modifying effects that alter the spontaneous SPW-HFO complexes generated by the hippocampal CA3 region of KO mice in vitro using extracellular multielectrode array recordings. We found that KD treatment significantly attenuated the pathologic features of KO SPWs and ripples and reduced the incidence of fast ripples. The KD also improved spike-timing reliability of KO CA3 principal cells, decreased mossy fiber excitability, increased mossy fiber-CA3 paired pulse ratios and reduced EPSP-spike coupling in the CA3 region. Collectively, these data indicate that KD treatment modulates CA3-generated pathologic oscillations by dampening hyperactive mossy fiber synapses.